Utility of chest x‐ray for tracheostomy tube placement in pediatric patients - Oliver S. Zhao; April Peterson; Kalpnaben Patel; Lyndy Wilcox (Laryngoscope Investigative Otolaryngology, 2024)
Abstract Objective To evaluate the utility of ordering chest x‐rays after pediatric tracheostomy tube placement in identifying acute, post‐operative complications and how it impacts clinical decision‐making. Methods In this retrospective cohort study, we identified tracheostomies performed in 139 pediatric patients through CPT codes over a 5‐year period from 2013 to 2018. Manual chart review was performed for demographic and clinical characteristics, pre‐procedure and post‐procedure chest x‐ray interpretations, and the presence of complications. Each complication was reviewed to see if action was taken due to post‐procedure chest x‐ray findings. Multivariable logistic regression was performed to determine associations with changes in pre‐procedure versus post‐procedure chest x‐rays. Results In a cohort of 139 pediatric patients with pre‐procedure and post‐procedure chest x‐rays, 40 (28.8%) of patients had new significant post‐procedure chest x‐ray findings compared to pre‐procedure chest x‐ray findings. Of these 40 instances of changes in pre‐procedure versus post‐procedure chest x‐ray findings, only eight resulted in action being taken due to the observed findings. Among these eight instances of action being taken, only one instance involved in invasive action being taken with a bronchoscopy. With multivariable regression analysis, patient age, race, gender, and the presences of genetic syndromes, were not found to be significant risk factors in predicting changes in pre‐procedure versus post‐procedure chest x‐ray. Conclusion In our study, post‐procedure chest x‐ray after tracheostomy tube placement did not significantly impact clinical decision making. It may be worth reconsidering the value in routine chest x‐rays after tracheostomy tube placement in pediatric patients.